2005
DOI: 10.1161/01.atv.0000168914.85107.64
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine Phosphorylase Gene Transfer Inhibits Vascular Smooth Muscle Cell Proliferation by Upregulating Heme Oxygenase-1 and p27 KIP1

Abstract: Objective-Thymidine phosphorylase (TP) reportedly promotes endothelial cell migration and induces heme oxygenase (HO)-1 expression. However, its effect on vascular smooth muscle cells (VSMCs) is poorly understood. In this study, we examined the effect of TP on VSMCs in vitro and in vivo. Methods and Results-Phagemid vector encoding human TP gene was transfected into rat VSMCs, and a clone overexpressing TP was selected (C2). C2 showed a slower migration and proliferation than VSMCs cloned with empty vector (pC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…We also found that TYMP inhibited vascular smooth muscle cell (VSMC) proliferation and migration 1113 . The inhibitory role of TYMP on VSMC is partly mediated by regulating the phosphorylation of Lyn 12 , an important non-receptor tyrosine kinase of the Src family.…”
Section: Introductionmentioning
confidence: 74%
“…We also found that TYMP inhibited vascular smooth muscle cell (VSMC) proliferation and migration 1113 . The inhibitory role of TYMP on VSMC is partly mediated by regulating the phosphorylation of Lyn 12 , an important non-receptor tyrosine kinase of the Src family.…”
Section: Introductionmentioning
confidence: 74%
“…Thus far, coexpression of TP and HO-1 has already been reported in clinical specimens of human malignant vertical growth melanomas in macrophages [29]. Studies in vitro implicated that HO-1 could only play a role downstream of TP, as was described in vascular smooth muscle cells or bladder carcinoma, where TP overexpression resulted in induction of HO-1 expression [5], [30]. We provide here mechanistic data showing that the regulation is indirect, potentially involving modulation of oxidative status of the cell, as the effects of Nrf2 or HO-1 on TP expression were mimicked by treatment of control cells with an antioxidant N-acetylcysteine.…”
Section: Discussionmentioning
confidence: 99%
“…15,[27][28][29] We used gene transfection of human PD-ECGF/TP into rat VSMCs to study the mechanism of inhibitory effect of PD-ECGF/TP on VSMC, and found that inhibition of VSMC proliferation was correlated with the upregulation of p27 KIP1 and HO-1. 15 We also found that adventitial gene transfer of TP/PD-ECGF in a balloon injury rat carotid artery model markedly inhibited the intimal hyperplasia. Interestingly, another group also reported that the addition of the PD-ECGF/TP protein into the cultured media inhibited DNA synthesis of cultured VSMCs in vitro, 30 suggesting the repeatable inhibitory effect of PD-ECGF/TP on VSMC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanisms may include, at least in part, upregulation of heme oxygenase-1 (HO-1) expression and consequently increased p27 KIP1 in cultured VSMCs. 15 These observations strongly suggest that PD-ECGF/TP gene therapy might have an effect on preventing vein graft failure by reducing intimal thickness. In the present study, we demonstrated for the first time to our knowledge that adventitial gene administration of PD-ECGF/TP significantly decreased the proliferative VSMC in the hyperplastic intima and markedly inhibited neointimal thickening of vein graft.…”
mentioning
confidence: 89%